Sinergi Perguruan Tinggi dan Masyarakat Sipil dalam Meningkatkan Partisipasi Politik Inklusif pada Pilkada - Erfain Erfain; St. Jawiah; Arsalim Arsalim; Risman Togala (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Political participation is a key indicator of a healthy and inclusive democracy. However, in the run-up to the Regional Head Elections (Pilkada), the phenomenon of apathy and political exclusion towards vulnerable groups such as women, people with disabilities, and new voters is still a serious challenge. This community service activity aims to build synergy between universities and civil society in encouraging inclusive political participation. Through strategic collaboration, political training and education programs are provided to communities in areas vulnerable to low participation. The methods used include identification of local actors, participatory approaches, interactive workshops, and community assistance. Interim results show an increase in community understanding of political rights and active involvement in public discussions and election simulations. This synergy shows that the involvement of higher education actors and NGOs can strengthen the capacity of grassroots democracy. This article recommends the need for sustainable policies and program replication in other areas as part of community-based democracy education.